Effect Analysis Of Benefit Perception, Ease Perception, Security And Risk Perception Of Merchant Interest In Using Quick Response Indonesia Standard (Qris) - Musa F. Silaen; Sepbeariska Manurung; Christine D. Nainggolan (Publisher Cv. Inara, 2021)
The purpose of this research is to analyze the effect of benefit perception, ease perception, security and risk perception of merchant interest in using Quick Response Indonesia Standard (QRIS) simultaneously or partially. The research variables consist of, X1 is benefit perception X2 is easy perception, X3 is security, X4 is risk perception and Y is merchant interest in using QRIS. Research data is Primary Data, obtained from the results of the distribution of questionnaires designed with the scale likert. The sample of the research was the merchant in pematangsiantar. Test Instruments using Test validity and reliability using SPSS. Technique Analysis, Multiple Regression, Classic Assumption Test, Hypothesis Test (Test F and Test t). The result showed that benefit perception has no significant effect on merchant interest using QRIS, the easy perception has no significant effect on merchant interest using QRIS, the security has significant effect on merchant interest using QRIS and the risk perception has significant effect on merchant interest using QRIS.